Mutant analysis in Arabidopsis provides insight into the molecular mode of action of the auxinic herbicide dicamba - Gleason, C.; Foley, R.; Singh, Karambir (Public Library of Science, 2011)
Herbicides that mimic the natural auxin indole-3-acetic acid are widely used in weed control. One common auxin-like herbicide is dicamba, but despite its wide use, plant gene responses to dicamba have never been extensively studied. To further understand dicamba's mode of action, we utilized Arabidopsis auxin-insensitive mutants and compared their sensitivity to dicamba and the widely-studied auxinic herbicide 2,4-dichlorophenoxyacetic acid (2,4-D). The mutant axr4-2, which has disrupted auxin transport into cells, was resistant to 2,4-D but susceptible to dicamba. By comparing dicamba resistance in auxin signalling F-box receptor mutants (tir1-1, afb1, afb2, afb3, and afb5), only tir1-1 and afb5 were resistant to dicamba, and this resistance was additive in the double tir1-1/afb5 mutant. Interestingly, tir1-1 but not afb5 was resistant to 2,4-D. Whole genome analysis of dicamba-induced gene expression showed that 10 hours after application, dicamba stimulated many stress-responsive and signalling genes, including those involved in biosynthesis or signalling of auxin, ethylene, and abscisic acid (ABA), with TIR1 and AFB5 required for the dicamba-responsiveness of some genes. Research into dicamba-regulated gene expression and the selectivity of auxin receptors has provided molecular insight into dicamba-regulated signalling and could help in the development of novel herbicide resistance in crop plants.